Fenomena Meme dan Ruang Publik Dalam Media Sosial - R Firdaus Wahyudi (Al-MUNZIR, 2022)
Social media is communication space allowing person to discus about an issue, especially public issues interactively. One of the unique social media messages is Meme. Meme is a term in explaining a phenomenon of communication messages by modified images, text and so on to convey the messages, views, opinions to the ideology of the creator. Memes spread and become viral through redistribution by other. This article aims to explain memes and its spreading (mimetic communication) in the social media. The main source of this research is a book entitled “communicating with memes: consequences in post truth civilization” written by Grant Kien. From analysis of this book, then it is used to describes the phenomena of Memes in the virtual public sphere. The results of analysis show that memes are a manifestation of the the social media development. Social media allows each individual have freedom to design and create the content of social media especially memes. Memes is a messages that created by individuals intentionally, then it is distributed in social media with various characters and functions. In the virtual public space, memes is used to convey messages regarding the Creator’s and disseminator’s view, stance and opinion about social issues. However, memes sometimes tend to break the standard of ethic, might get offensive for some people, and shallow. Keywords :Memes, Social Media And Virtual Public Speher